2010
DOI: 10.1111/j.1467-9922.2010.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Learned Attention Effects in L2 Temporal Reference: The First Hour and the Next Eight Semesters

Abstract: This article relates adults' difficulty acquiring foreign languages to the associative learning phenomena of cue salience, cue complexity, and the blocking of later experienced cues by earlier learned ones. It examines short-and long-term learned attention effects in adult acquisition of lexical (adverbs) and morphological cues (verbal inflections) for temporal reference in Latin (1 hr of controlled laboratory learning) and Spanish (three to eight semesters of classroom learning). Our experiments indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 53 publications
9
54
0
Order By: Relevance
“…As such, this study represents a first step in identifying ways that researchers and language instructors can harness pronunciation training to benefit L2 learning in other linguistic domains, including grammar. Future research should identify precisely when it is best to introduce such training—after learners already have basic knowledge of the target structure, as in the present study, or the very first time a particular structure is introduced in the curriculum (compare Doughty, ; Ellis & Sagarra, ; Jourdenais et al, )—how such training would transfer to other L2 forms and in other languages, and whether such pronunciation training could lead to significant benefits even in the absence of explicit grammar instruction. Nevertheless, findings from this study suggest that pronunciation training not only leads to gains in L2 pronunciation, but also has the potential to facilitate both immediate and longer‐term L2 learning more generally.…”
Section: Resultsmentioning
confidence: 94%
“…As such, this study represents a first step in identifying ways that researchers and language instructors can harness pronunciation training to benefit L2 learning in other linguistic domains, including grammar. Future research should identify precisely when it is best to introduce such training—after learners already have basic knowledge of the target structure, as in the present study, or the very first time a particular structure is introduced in the curriculum (compare Doughty, ; Ellis & Sagarra, ; Jourdenais et al, )—how such training would transfer to other L2 forms and in other languages, and whether such pronunciation training could lead to significant benefits even in the absence of explicit grammar instruction. Nevertheless, findings from this study suggest that pronunciation training not only leads to gains in L2 pronunciation, but also has the potential to facilitate both immediate and longer‐term L2 learning more generally.…”
Section: Resultsmentioning
confidence: 94%
“…As reported in Leow (2012a), up to the mid 1990s, it had generally been assumed that experimental conditions (instruction or exposure) produced the required attention to the targeted item(s) in the L2 input. In addition to these strands, there have been several recent studies (e.g., Ellis 2006;Ellis & Sagarra 2010a, 2010bEllis et al 2014) that have purported to investigate the concept of LEARNED attention (Denton & Kruschke 2006) and the phenomenon of blocking. Indeed, most major theoretical underpinnings in SLA (e.g., McLaughlin 1987;Tomlin & Villa 1994;Robinson 1995;Gass 1997;Schmidt 2001;VanPatten 2004) postulate an important role for learner attention to any L2 exposure, be it aural or written, manipulated or authentic.…”
Section: Background: Attentionmentioning
confidence: 99%
“…Furthermore, he found that study abroad learners with higher working memory capacity were better able to focus on morphological cues. In order to determine whether the learners' bias towards lexical cues is a general characteristic of the early stages of L2 learning or whether it is due to L1 transfer, Sagarra, Ellis & Gauthier (2011) asked English-Spanish and Romanian-Spanish late learners and three control groups (English, Romanian and Spanish monolinguals) to read similar sentences to those employed in Ellis & Sagarra (2010) in L2 Spanish (or their L2 for the controls) and choose one of four pictures after each sentence (two competing for meaning and two for form). The results revealed that (1) beginning learners relied so heavily on adverbs that they were insensitive to adverb-verb tense incongruencies unless they had high working memory capacity, (2) intermediate learners were sensitive to tense incongruencies but still relied more on adverbs independently of whether their L1 had impoverished (English) or rich (Romanian) morphology, and (3) advanced learners were sensitive to tense incongruencies, but those with L1 English relied more on adverbs whereas those with L1 Romanian relied more on verbs.…”
Section: Morphological Processingmentioning
confidence: 99%
“…With regard to verbal morphology, Ellis & Sagarra (2010) asked low proficiency English-Spanish adult learners to read sentences in Spanish (Spanish and English control groups read sentences in their L1) containing adverb-verb and verb-adverb congruencies/incongruencies and answer a comprehension question after each sentence. The findings suggested that native speakers of a morphologically rich language (Spanish monolinguals) rely more on morphological than lexical cues to resolve grammatical conflicts, and that, contrariwise, native speakers of a morphologically impoverished language (English monolinguals and late English-Spanish learners) behave the opposite way.…”
Section: Morphological Processingmentioning
confidence: 99%